2012
DOI: 10.1007/s00296-012-2589-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hyperuricemia and its correlates in an inland Chinese adult population, urban and rural of Jinan

Abstract: Economy has developed rapidly in China, and the clustering of cardiovascular risk factors in subjects increased remarkably over the past two decades. However, no data are available regarding the temporal prevalence of hyperuricemia and its correlates in this rapidly developing area, especially in the inland area. The cross-sectional survey was based on a random sample of 4,218 residents aged 35-64 years in the Jinan area. Hyperuricemia was defined as serum uric acid ≥ 416 μmol/L in men and ≥ 357 μmol/L in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
8
18
1
Order By: Relevance
“…[44][45][46] Studies in rodents and other molecular observations indicate an important role for SLC2A9 in proximal tubular urate absorption. 47,48 Genome-wide (GWAS) and candidate association studies have found strong association of SLC2A9 SNPs with SUA levels.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Studies in rodents and other molecular observations indicate an important role for SLC2A9 in proximal tubular urate absorption. 47,48 Genome-wide (GWAS) and candidate association studies have found strong association of SLC2A9 SNPs with SUA levels.…”
Section: Discussionmentioning
confidence: 99%
“…11,[21][22][23] The mechanism underlying the slightly lower prevalence of hyperuricemia in males aged ≥85 than in those aged 75-84 years remains unclear; nevertheless, in females, the increase in hyperuricemia prevalence with increasing age may be explained by postmenopausal changes in the endocrine system and estrogen levels. 22 Consistent with other studies, 21,22,25 we observed a positive association between hyperuricemia and metabolic disorders in our Chinese population. Epidemiological studies have also reported an association between hyperuricemia and metabolic disorders such as metabolic syndrome, hyperlipidemia, obesity, and type 2 diabetes.…”
Section: 11-14mentioning
confidence: 99%
“…Epidemiological studies have also reported an association between hyperuricemia and metabolic disorders such as metabolic syndrome, hyperlipidemia, obesity, and type 2 diabetes. 11,22,25 Metabolic syndrome is a cluster of three diseases-hypertension, hyperglycemia, and gout, 11 Although metabolic syndrome is clearly associated with obesity, insulin resistance, and abnormal blood lipids, which lead to the three diseases, the etiological mechanisms of this 26 Previous studies have indicated that serum uric acid level can be used as a crucial predictor of metabolic syndrome and that the number of metabolic syndrome components increases the prevalence and OR for significantly increased uric acid activity. 11,27,28 Among patients with chronic hepatitis, fructose load may cause a substantial increase in serum uric acid levels.…”
Section: 11-14mentioning
confidence: 99%
See 2 more Smart Citations